2020
DOI: 10.1111/tme.12671
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 infection in sickle cell disease: An analysis from the Centers for Disease Control haemoglobinopathy blood surveillance project

Abstract: Summary Objective In the multicentre Haemoglobinopathy Blood Surveillance Project, to evaluate the seroprevalence of parvovirus B19 and DNA viral load in sickle cell disease (SCD). Background Although the epidemiology of parvovirus B19 seropositivity in SCD has been well documented, there are few studies that have assessed possible persistent parvovirus DNAemia and associated risk factors including blood transfusion. Methods A qualitative analysis of parvovirus B19 serology using ELISA and quantitative parvovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Regarding haematological affliction, a higher incidence of BMF was noted in the present study compared to previous reports 3,15 . BM examinations of our present cohort with pancytopenia showed several forms.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Regarding haematological affliction, a higher incidence of BMF was noted in the present study compared to previous reports 3,15 . BM examinations of our present cohort with pancytopenia showed several forms.…”
Section: Discussioncontrasting
confidence: 60%
“…Regarding haematological affliction, a higher incidence of BMF was noted in the present study compared to previous reports. 3,15 BM examinations of our present cohort with pancytopenia showed several forms. Our findings support the previous reports that HPV-B19 did not target erythroid progenitor cells only, which may lead to TAC 16 and myelodysplasia, 17 but also non-erythroid cells such as megakaryocytes and leucocytic cells could be affected.…”
Section: Discussionmentioning
confidence: 57%
“…Although parvovirus B19 DNA regularly persists in different tissues, reactivation and replication are unlikely in this virus type. Studies have shown that the risk of acquiring a parvovirus B19 infection is greater during the 1st year post-engraftment and can be related to the use of red blood cell transfusions ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%